PENGGUNAAN TEKNOLOGI WEB UNTUK SISTEM E-LEARNING ADAPTIF DI PENDIDIKAN: SYSTEMATIC LITERATURE REVIEW 2020–2025 - Andi Nurwafia; Iin Sugiarti; Nia Rahmadani; Sri Rejeki; Dhimas Tribuana (Plexi Digital Indonesia, 2025)
This study aims to synthesize recent findings on the use of web technologies in adaptive e-learning systems in education and to identify the main research themes, benefits, and implementation challenges. The development of web technology has significantly influenced the evolution of e-learning systems, particularly in creating adaptive learning environments that cater to individual student needs. This study employs a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework to analyze 40 relevant articles published between 2020 and 2025 The review identifies key themes, including web-based architectures, adaptive algorithms and personalization, learning analytics, user experience, and implementation and adoption challenges. The findings highlight that adaptive e-learning systems The findings indicate that adaptive e-learning systems can increase course completion and engagement by up to 40% and reduce learning time by around 30% while improving knowledge retention. However, challenges related to data privacy, infrastructure limitations, interoperability, and limited teacher training, as well as concerns about algorithmic transparency and ethics, remain significant barriers to widespread adoption. This study proposes a five-layer conceptual model that integrates technology infrastructure, data and intelligence components, pedagogical design, and user-centric interfaces to guide the development of effective adaptive e-learning systems.